Sustainable supplies of quality herbage seed for sub-Saharan Africa smallholders - Griffiths, R. (New Zealand Grassland Association, 1993)
Sub-Saharan Africa herbage seed activities were evaluated by means of questionnaires. Topics ranged from collection and evaluation, through multiplication to distribution and seed quality. The current smallholder lack of access to herbage seed supplies is discussed and proposals for overcoming this problem submitted for consideration by those concerned.